PENERAPAN INTERNET OF THINGS PADA PEMANTAUAN OTOMATIS SUHU DAN KELEMBABAN TANAMAN HIDROPONIK MENGGUNAKAN RASPBERRY PI - Ery Murniyasih; Luluk Suryani; Hieronimus Fidel Maria Rahawarin (Politeknik Bisnis Indonesia, 2023)
The implementation of Internet of Things technology is still being developed, for example in the agricultural sector, namely hydroponics. Hydroponics is a planting technique without soil, this technique provides opportunities for farmers who have limited land but still produce quality plants. This research aims to apply the Internet of Things to automatically monitor the temperature and humidity in a Raspberry pi 3-based hydroponic room. It is hoped that this will increase farmers' knowledge in maintaining the temperature and humidity conditions in the planting room. The method used in the process of detecting the temperature and humidity conditions of the hydroponic room is using a DHT22 sensor, then using a water spray base mist sprayer and an automatic fan to maintain the temperature and humidity of the room which is controlled using an Arduino Mega 2560 with a Raspberry pi as a server device, to run the website as an independent platform that monitors and controls online temperature and humidity based on IoT. The result of this research is a control device that can be used to monitor and maintain the temperature of the hydroponic room ≤ 270C up to and maintain air humidity with a minimum limit of up to 65%.